EFFECTIVENESS OF MICRO-PRODUCING BUSINESS (BPUM) PRODUCTIVE BANPRES PROGRAM IN INCREASING THE PRODUCTIVITY OF MICRO, SMALL, AND MEDIUM BUSINESS (UMKM) IN SUKABUMI CITY DURING THE COVID-19 PANDEMIC - Fitria Ayu Handayani; Rizki Hegia Sampurna; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The Effectiveness of the Productive Presidential Assistance Program for Micro Enterprises (BPUM) in Increasing the Productivity of Micro, Small and Medium Enterprises (MSMEs) in Sukabumi City During the Covid-19 Pandemic. The purpose of this research is to find out and describe the effectiveness of the Productive Presidential Assistance Program for Micro Enterprises (BPUM) in Sukabumi City and the inhibiting factors in its implementation. This is motivated by the fact that there are still problems related to the BPUM Presidential Decree, namely the occurrence of double data or duplicates, and many of the BPUM Presidential Decrees are not on target. This study used qualitative research methods. Informants in this study were the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry (Diskopdagrin) of Sukabumi City, as well as the community/SMEs who received the BPUM Presidential Assistance program. Data validation in this study used source triangulation and technique triangulation. The results of this study are that the BPUM presidential assistance program in increasing the productivity of MSMEs in Sukabumi City has been running effectively, but there are still obstacles, namely that it is not fully on target because there are BPUM recipients who do not have a business to participate in getting this assistance.